Characterization of bioactive compounds produced by endophytic fungi isolated from Gynura procumbens (Sambung Nyawa) - Haifa Arghnia, A. Jamal; Ahmad, Husaini; Ngui Sing, Ngieng; Hairul Azman, Roslan; Azham, Zulkharnain; Wahab Abideen, Akinkunmi (Springer Nature, 2022)
This research evaluates the bioactivity of twelve endophytic fungi successfully isolated and characterised from Gynura procumbens. The fungal extracts displayed inhibitory activity against Staphylococcus aureus, Pseudomonas aeruginosa, Methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli and Salmonella typhi with the MIC and MBC of 5000 µg/mL. High antioxidant activity using DPPH free radical scavenging assay with inhibition of 86.6% and IC50 value of 104.25 ± 18.51 µg/mL were exhibited by ethyl acetate extract of Macrophomina phaseolina SN6. In contrast, the highest scavenging activity percentage of methanolic extract was exhibited by Mycoleptodiscus indicus SN4 (50.0%). Besides that, the highest ferric reducing antioxidant power (FRAP) value of ethyl acetate and methanolic extract was recorded from M. phaseolina SN6 (239.9 mg Fe (II)/g) and M. indicus SN4 (44.7 mg Fe (II)/g), respectively. Total phenolic content (TPC) and total flavonoid content (TFC) of ethyl acetate and methanolic fungal extracts were determined using Folin-Ciocalteu and aluminium chloride, respectively. The highest TPC for ethyl acetate and methanolic extracts were exhibited by Colletotrichum gloeosporioides SN11 (87.0 mg GAE/g) and M. indicus SN4 (35.0 mg GAE/g), whereas the highest TFC of ethyl acetate and methanolic extracts were showed by M. phaseolina SN6 (122.8 mg QCE/g) and M. indicus SN4 (60.4 mg QCE/g), respectively. Bioactive metabolites of isoelemicin (50.8%), terpinen-4-ol (21.5%), eucalyptol (24.3%), oleic acid (19.8%) and β-pinene (10.9%) were detected. Owing to the higher content of phytochemicals represented in the ethyl acetate extract of M. phaseolina, SN6 is therefore identified to be a superior candidate in exhibiting strong antioxidant and antimicrobial properties be fit for further pharmaceutical studies.